2000
DOI: 10.1159/000018423
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides: Review of Epidemiological Observations

Abstract: Background: Mycosis fungoides (MF) is a chronic cutaneous T-cell lymphoma characterized by small cells with cerebriform nuclei that usually express a mature peripheral T-helper cell (CD4+) immunophenotype. Its evolution is typically quite slow, with years between the first manifestations and development of advanced stages of disease. Objective: The purpose of the present paper is to contribute to the material about MF already present in the literature. The review articles that have appeared to date fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
3
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 23 publications
5
36
3
8
Order By: Relevance
“…Blacks had statistically higher IR of CTCL and MF than other races, consistent with previous studies. 4,26 To our knowledge, for the first time we reported that the CTCL IRs among Asian/ Pacific Islanders and Hispanic whites were lower than among blacks and non-Hispanic whites. In contrast to MF, IRs for primary cutaneous peripheral T-cell lymphoma and cutaneous CD30 ϩ T-cell lymphoproliferative disease were similar among blacks and nonHispanic whites.…”
Section: Discussionmentioning
confidence: 71%
“…Blacks had statistically higher IR of CTCL and MF than other races, consistent with previous studies. 4,26 To our knowledge, for the first time we reported that the CTCL IRs among Asian/ Pacific Islanders and Hispanic whites were lower than among blacks and non-Hispanic whites. In contrast to MF, IRs for primary cutaneous peripheral T-cell lymphoma and cutaneous CD30 ϩ T-cell lymphoproliferative disease were similar among blacks and nonHispanic whites.…”
Section: Discussionmentioning
confidence: 71%
“…At this time, it is impossible to predict which patients with early-stage CTCL will progress, and which will continue to manifest indolent skin-limited disease. 9 Transcriptional analysis of cancer has proven to be a powerful and increasingly useful tool in biomedical research. [10][11][12] These patterns of gene expression have revealed unappreciated complexity in histologically homogeneous diseases like large-cell B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…The MF incidence is about 3 per million a year, affecting people between 55 to 60 years of age (2). The disease may have a slow, indolent evolution and causes skin lesions that include nodules, plaques, and tumors that can progress to compromise an extensive area of skin (3).…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare disease, of low incidence, and usually affects middle-aged men (2). In most cases, only the skin is involved (3), although in advanced stages it may present with extracutaneous involvement, including the gastrointestinal tract (4,5).…”
Section: Introductionmentioning
confidence: 99%